The Virulence Polysaccharide of Salmonella Typhi Suppresses Activation of Rho Family GTPases to Limit Inflammatory Responses From Epithelial Cells - Parween, Farhat; Yadav, Jitender; Qadri, Ayub (Frontiers in Cellular and Infection Microbiology, 2019)
Vi capsular polysaccharide (Vi) is a major virulence factor of human typhoid-causing pathogen Salmonella enterica serovar Typhi (S.Typhi). It distinguishes S.Typhi from closely related non-typhoidal Salmonella serovars such as S.Typhimurium which do not normally cause systemic infection in humans. Vi not only forms a capsule around S.Typhi but it is also readily released from this pathogen. We have previously reported that Vi targets prohibitin to inhibit cellular responses activated through immune receptors. Here, we show that engagement of membrane prohibitin with Vi prevents Salmonella-induced activation of small Rho-family GTPases, Rac1 and Cdc42, and suppresses actin cytoskeletal rearrangements resulting in reduced invasion and highly subdued inflammatory responses. Cells infected with S.Typhimurium in presence of Vi show poor activation of NF-kB and MAP-kinase pathways of intracellular signaling. Treatment with Vi brings about redistribution of Rac-1, prohibitin and ganglioside GM1 in membrane raft domains. Vi-mediated interference with activation of Rho-family GTPases represents a previously unrecognized mechanism by which S.Typhi can limit its invasion and alarming of the host.